2014
DOI: 10.1186/1471-2407-14-810
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of colorectal liver metastases in Germany: a ten-year population-based analysis of 5772 cases of primary colorectal adenocarcinoma

Abstract: BackgroundPurpose of this study was to analyse the surgical management and long-term clinical outcome of patients diagnosed with colorectal liver metastases (CLM) over a period of 10 years using data from a German tumour registry.MethodsRetrospective analysis of 5772 patients diagnosed with colorectal adenocarcinoma between 2002 and 2007. Follow-up was continued until 2012.Results1426 patients (24.7%) had CLM; 1019 patients (71%) had synchronous, 407 patients (29%) developed metachronous CLM. Hepatic resection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
184
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(203 citation statements)
references
References 20 publications
5
184
3
Order By: Relevance
“…This is an optimistic number, but considering that criteria for resection of LM and extrahepatic disease are moving targets, resection rates in this order might be reached in a not too distant future. This is in part supported by other population‐based studies in which an increase in resection rates was observed over time to above 30% in patients diagnosed during 2007 .…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This is an optimistic number, but considering that criteria for resection of LM and extrahepatic disease are moving targets, resection rates in this order might be reached in a not too distant future. This is in part supported by other population‐based studies in which an increase in resection rates was observed over time to above 30% in patients diagnosed during 2007 .…”
Section: Discussionsupporting
confidence: 78%
“…Initially, unresectable liver metastases can be rendered resectable by combinations of tumor‐directed interventions and future liver remnant manipulation . Improvement in imaging technology, surgical and interventional techniques, and oncologic therapy have increased the observed resection rate to approximately 25%, as reported in population‐based materials .…”
Section: Introductionmentioning
confidence: 99%
“…Only 20% to 30% of patients with CRC metastases confined to the liver are candidates for surgery (2,4). In others, extensive tumor burden within the liver or poor anatomical position of the tumors close to critical vascular or biliary structures precludes resection.…”
mentioning
confidence: 99%
“…There is no standard definition of “synchronous metastases” in the literature. In clinical trials and population registries, the interval defining “synchronous” metastatic disease generally spans 0 to 12 months after diagnosis . For the purposes of this review, we will refer to the clinical problem as “simultaneous metastases,” that is, known liver metastatic disease at presentation.…”
Section: Introductionmentioning
confidence: 99%